Peran Orangtua Dalam Pendampingan Persiapan Komuni Pertama Di Stasi St. Benedictus Teluk Siak Estate Paroki St. Yohanes Pembaptis Perawang - Theresia Yulinda Araujo; Yustinus Joko Wahyu Yuniarto; Hartutik Hartutik (Publisher STPKat, 2022)
The role of parent at st. Benedictus gulf of Siak Estate is less serious than entertaining the Catholic faith in paiding. preparing children for the first communion. Often children who should be able to receive communion are, in fact, unable to accept it because parents are busy with their work or the child himself is not asking the parents to take the first communion preparation. Research aims to review the practical roles of parents with children, to know inhibitors and supportive factors and to know the steps to improving parenting. Research of qualitative methods with this descriptive approach scores the data trianulation. With the respondent's parents of the first communion candidate. Data collection techniques using interviews, and documentation, and observations. Research indicates that parents perform a child's side by taking part in the first communion study, inviting children to the celebration of the Eucharist and teaching reverence before and after receiving holy communion, and actively inviting children to join spiritual activities in the church, both in the ward and at home. The barriers that parents experience are sometimes forgetting to remind children follow communion study and the difficulty of teaching children to manage time between play and learning. Supporting factors of parents have teachers and catechism and the first communion handbook and facilitate transportation. Parish priest and caretaker of gere